The Influence of Residential Environment on the Character Formation of University Students: A Case Study of UTHM Pagoh, Johor, Malaysia - Kirin, Arwansyah; Khairuddin, Khairuddin (Abdurrauf Social Science, 2025)
The residential environment plays a pivotal role in shaping students’ character, yet empirical studies in Malaysia particularly in semi-rural campuses such as UTHM Pagoh remain scarce. The shifting lifestyles of students living away from their families highlight the urgent need to examine how physical conditions, social interactions and prevailing norms within their residential settings influence character formation. This study aims to analyze the impact of residential environment on the character development of UTHM Pagoh students. Employing a quantitative survey design with 304 respondents, data were analyzed using simple regression via SPSS 25. The findings reveal that the residential environment has a statistically significant effect on students’ character (0,000 < 0,05), although its contribution is relatively small (8.6%). These results affirm that residential factors while not dominant, remain integral in shaping students’ moral behavior alongside family background, digital media and academic engagement. Theoretically, this study expands the discourse on character education by highlighting the often-overlooked role of residential context. Practically, the implications offer valuable insights for universities and policymakers in designing dormitory environments and character-building programs that are more conducive, inclusive and effective. [Lingkungan tempat tinggal memainkan peran penting dalam membentuk karakter mahasiswa, namun kajian empiris di Malaysia khususnya pada kampus semi-pedesaan seperti UTHM Pagoh masih sangat terbatas. Perubahan gaya hidup mahasiswa yang tinggal jauh dari keluarga menimbulkan kebutuhan mendesak untuk menilai sejauh mana kondisi fisik, interaksi sosial dan norma di lingkungan tempat tinggal memengaruhi pembentukan karakter mereka. Oleh karena itu, penelitian ini bertujuan untuk menganalisis pengaruh lingkungan tempat tinggal terhadap karakter mahasiswa UTHM Pagoh. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei terhadap 304 responden dan data dianalisis menggunakan regresi sederhana melalui SPSS 25. Hasil penelitian menunjukkan bahwa lingkungan tempat tinggal berpengaruh signifikan terhadap pembentukan karakter mahasiswa yaitu 0,000 < 0,05, meskipun kontribusinya relatif kecil yaitu sebesar 8,6%. Temuan ini menegaskan bahwa faktor lingkungan tempat tinggal tetap penting sebagai salah satu elemen pembentuk karakter di samping pengaruh keluarga, media digital dan interaksi akademik. Secara teoritis, penelitian ini memperkaya literatur pendidikan karakter dengan menekankan dimensi residensial sebagai faktor yang sering diabaikan. Secara praktis, implikasinya dapat dijadikan rujukan bagi pihak universitas maupun pembuat kebijakan dalam merancang lingkungan asrama serta program pengembangan karakter yang lebih kondusif, inklusif dan efektif.]